Umfragestudie „Update Neurointensiv Deutschland 2012“: Struktur, Standards und Scores auf deutschen Neurointensivstationen = Survey study: update on neurological intensive care in Germany 2012 : structure, standards and scores in neurological intensive care units - Bösel, Julian; Kahmann, Janine (Der Nervenarzt, 2012)
SummaryBackgroundNeurological critical care lacks high-quality evidence to guide optimal treatment. Furthermore, it is presently rather unclear as to what extent German neurological intensivists adhere to guidelines, employ standard operating procedures or use scoring tools.MethodsAn e-mail-based questionnaire was distributed to physicians directing German neurological, neurosurgical and neurological/neurosurgical interdisciplinary intensive care units (ICUs).ResultsOf the 326 departments 78 answered the questionnaire and of these 53% were university units. The ICUs were either led by neurologists (37%), neurosurgeons (22%), anesthetists (28%) or a combination of these (13%). The mean number of ICU beds was 11.2 and the mean number of intensivists 7.7. Guideline adherence was stated to amount to 75 % by 41 % of the ICUs. Applications of standard procedures was achieved by more than 80 % for several ICU management aspects, while only 5 out of 19 of the respondents routinely used scoring tools in > 60% of the ICUs. The extent of protocol and score applications differed significantly according to hospital status or leading speciality.ConclusionThis survey suggests an obvious interest in but also an unfulfilled need of guidance in a standardized approach to neurological critical care in Germany. More activity in multicentre clinical research with a neurocritical focus to provide optimization of protocols, scores and guidelines appears to be warranted.
Online publiziert: 10. Dezember 2012
Auf der Frontdoor mit Publikationsdatzum 08. Dezember 2012
Gesehen am 15.10.2018